GLOBAL MINDSET IN GLOBAL LEADERS: How to Develop It and Which Individual Factors Affect the Process? - Wahlbeck, Emilia (My University, 2014)
The modern globalised business world requires new kinds of leaders and employees. As organisations’ successfulness is rather dependent on effective leadership, it is of the upmost importance to be able to find and develop leaders who can thrive in today’s complex and multicultural business environment. The key factor that is suggested to separate local and global managers is global mindset and in this thesis it is defined as having two distinct parts; cultural intelligence and global business orientation. Because there is no widely concurred definition for global mindset, this thesis will aim at studying how well the utilised definition matches with a definition offered by global leaders themselves. In addition, as companies are very motivated to find ways to detect and develop global mindset in their managers and overall employees, this thesis will concentrate on finding concrete ways to develop global mindset. Yet, it is not enough to know how to increase employees’ global mindset; companies do not have the resources to offer similar development initiates to their whole personnel. Therefore, organisations would gain from knowing who would benefit the most from a certain development method. Additionally, this thesis aims at finding individual factors that can affect a person’s ability and likelihood to develop global mindset. In order to reach these three research aims, this thesis will conduct a literature review concerning the development methods and individual factors and compare its results to an empirical data offered by ten qualitative semi-structured interviews with global leaders. As earlier research about these issues is rather limited, this thesis will utilise research conducted about global leadership and expatriate development.
Keywords: Global Mindset; Global Leadership Development; Individual Factors; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|